Timeliness metrics for screening and preventing TB in household contacts of pulmonary TB patients in Kenya - D. Nair; P. Thekkur; I. Mbithi; M. Khogali; R. Zachariah; S. Dar Berger; S. Satyanarayana; A. M. V. Kumar; I. Kathure; J. Mwangi; A. F. Bochner; A. McClelland; et al. (IJTLD Open)
BACKGROUND: The study assessed whether a “7-1-7” timeliness metric for screening and TB preventive therapy (TPT) could be implemented for household contacts (HHCs) of index patients with bacteriologically confirmed pulmonary TB under routine programmatic settings in Kenya. METHODS: A longitudinal cohort study conducted among index patients and their HHCs in 12 health facilities, Kiambu County, Kenya. RESULTS: Between January and June 2023, 95% of 508 index patients had their HHCs line-listed within 7 days of initiating anti-TB treatment (“First 7”). In 68% of 1,115 HHCs, screening outcomes were ascertained within 1 day of line-listing (“Next 1”). In 65% of 1,105 HHCs eligible for further evaluation, anti-TB treatment, TPT or a decision for no drugs was made within 7 days of screening (“Second 7”). Altogether, 62% of screened HHCs started TPT during the “7-1-7” period compared with 58% in a historical cohort. Main barriers to TPT uptake were HHCs not consulting clinicians, HHCs being unwilling to initiate TPT and drug shortages. Healthcare workers felt that a timeliness metric was valuable for streamlining HHC management and proposed “3-5-7” as a workable alternative. CONCLUSIONS: The national TB programme must generate awareness about TPT, ensure uninterrupted drug supplies and assess whether the “3-5-7” metric can be operationalised.